Single channel studies of the phosphorylation of K+ channels in the squid giant axon. II. Nonstationary conditions (The Rockefeller University Press, 1991)
The effects of phosphorylation on the properties of the 20-pS channel of the squid giant axon were studied using the cut-open axon technique. Phosphorylation of the channel was achieved by photoreleasing caged ATP (inside the patch pipette) in the presence of the catalytic subunit of the protein kinase A. An inverted K+ gradient (500 K+ external parallel 5 K+ internal) was used to study the activation process. Phosphorylation decreased the frequency of openings of the channel at most potentials by shifting the probability vs. voltage curve toward more positive potentials. The mean open times showed no voltage dependence and were not affected by phosphorylation. The distribution of first latencies, on the other hand, displayed a sharp voltage dependence. Phosphorylation increased the latency to the first opening at all potentials, shifting the median first latency vs. voltage curve toward more positive potentials. The slow inactivation process was studied in the presence of a physiological K+ gradient (10 K+ external parallel 310 K+ internal). Pulses to 40 mV from different holding potentials were analyzed. Phosphorylation increases the overall ensemble probability by decreasing the number of blank traces. A single channel inactivation curve was constructed by computing the relative appearance of blank traces at different holding potentials before and after photoreleasing caged ATP. As determined in dialyzed axons, the effect of phosphorylation consisted in a shift of the inactivation curve toward more positive potentials. The 20-pS channel has the same characteristics as the delayed rectifier current in activation kinetics, steady-state inactivation, and phosphorylation effects.